Microaggression against Asian Americans during the pandemic - Kim, Daniel Yoon Sik (Journal of ethnicity in criminal justice, 2025)
The COVID-19 pandemic led to a rise in hate incidents, including microaggressions, against Asian Americans, yet research on this issue remains limited. This study examines the relationship between demographic composition and microaggressions during the pandemic through minority-group threat theory, using Collaborative Multiracial Post-Election Survey (CMPS) data. Findings show that a higher immigrant population increases the likelihood of Asian Americans experiencing microassault and microinvalidation, while a larger Asian population decreases this likelihood. These results highlight the role of demographic factors in shaping anti-Asian microaggressions. The study contributes to the literature by addressing a gap in understanding the factors influencing microaggressions and discusses limitations and policy implications.